Analisis Faktor-Faktor yang Berhubungan Dengan Akses Air Minum Aman di Wilayah Kerja Dinas Kesehatan Kabupaten OKU Tahun 2021 - Maria Zora; Erma Gustina; Maria Ulfah (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2022)
One of the main needs of humans is drinking water. Every operation of drinking water that is produced must be safe for health if it meets the physical requirements and other parameters that measure whether the water is safe or not when consumed by the public.This study aims to determ ine the factors related to access to safe drinking water in the Ogan Komering Ulu District Health Office Work Area in 2021. The research design used was cross sectional. This research was conducted in the area of the Health Office of Ogan Komering Ulu Regency in March - July 2021. The population in this study was all access to drinking water at the Environmental Health Inspection in the Work Area of the Health Office of Ogan Komering Ulu Regency with a sample of 98 respondents.This study shows that there are 58 accesses to safe drinking water. Based on the bivariate analysis, it was found that there was a relationship between drinking water management (p value = 0.000), as well as containers before processing and ready-to-drink storage containers (p value = 0.000) with Access to Safe Drinking Water. Water in the Work Area of the Health Office of Ogan Komering Ulu Regency in 2021. Multivariately, the dominant variable with access to drinking water is the container for pre-processed and ready-to-drink water containers (p value = 0.004) and exp (B) of 6.568. The conclusion from these results, that there is a significant relationship with access to safe drinking water is drinking water facilities (59,2%), drinking water management (43.9%), sanitation and drinking water hygiene (58.2%), containers storage before processing and ready-to-drink water storage containers (33.7%) This study suggests that the Health Office of Ogan Komering Ulu Regency can increase knowledge by way of counseling and public health seminars, especially